Factors associated with extrajudicial arrest for syringe possession: results of a department-wide survey of municipal police in Tijuana, Mexico - Mario Morales; Claudia Rafful; Tommi L. Gaines; Javier A. Cepeda; Daniela Abramovitz; Irina Artamonova; Pieter Baker; Erika Clairgue; Maria Luisa Mittal; Teresita Rocha-Jimenez; Jaime Arredondo; Thomas Kerr; et al. (BMC, 2018)
Abstract Background Mexican law permits syringe purchase and possession without prescription. Nonetheless, people who inject drugs (PWID) frequently report arrest for syringe possession. Extrajudicial arrests not only violate human rights, but also significantly increase the risk of blood-borne infection transmission and other health harms among PWID and police personnel. To better understand how police practices contribute to the PWID risk environment, prior research has primarily examined drug user perspectives and experiences. This study focuses on municipal police officers (MPOs) in Tijuana, Mexico to identify factors associated with self-reported arrests for syringe possession. Methods Participants were active police officers aged ≥18 years, who completed a self-administered questionnaire on knowledge, attitudes and behaviors related to occupational safety, drug laws, and harm reduction strategies. Univariable and multivariable logistic regression was used to identify correlates of recent syringe possession arrest. Results Among 1044 MPOs, nearly half (47.9%) reported always/sometimes making arrests for syringe possession (previous 6mo). Factors independently associated with more frequent arrest included being male (Adjusted Odds Ratio [AOR] = 1.62; 95% Confidence Interval [95% CI] =1.04-2.52; working in a district along Tijuana River Canal (where PWID congregate) (AOR = 2.85; 95%CI = 2.16-3.77); having recently experienced a physical altercation with PWID (AOR = 2.83; 95% CI = 2.15-3.74); and having recently referred PWID to social and health services (AOR = 1.97; 95% CI = 1.48-2.61). Conversely, odds were significantly lower among officers reporting knowing that syringe possession is legal (AOR = 0.61; 95% CI = 0.46-0.82). Conclusions Police and related criminal justice stakeholders (e.g., municipal judges, prosecutors) play a key role in shaping PWID risk environment. Findings highlight the urgent need for structural interventions to reduce extra-judicial syringe possession arrests. Police training, increasing gender and other forms of diversity, and policy reforms at various governmental and institutional levels are necessary to reduce police occupational risks, improve knowledge of drug laws, and facilitate harm reduction strategies that promote human rights and community health.